2011
DOI: 10.1159/000322407
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in Central Pancreatectomy

Abstract: Background: Non-cancerous pancreatic lesions have been increasing, and function-preserving pancreatectomy may be an adequate approach to them. Recent advanced experience of major pancreatectomy has stimulated interest in central pancreatectomy (CP). Materials and Methods: Nineteen patients who underwent CP for benign and borderline malignant lesions of the pancreas from January 1990 to December 2007 were retrospectively reviewed. We also summarized recent literature reporting more than 10 cases of CP. Result: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Thus, CP appears to be a promising alternative in selected cases [30,31]. However, CP is an uncommon pancreatic resection (less than 3% of all pancreatic resections) even at high-volume centers [5,10,26,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, CP appears to be a promising alternative in selected cases [30,31]. However, CP is an uncommon pancreatic resection (less than 3% of all pancreatic resections) even at high-volume centers [5,10,26,32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies comparing CP to distal pancreatectomy have shown a significantly increased rate of postoperative pancreatic fistulae after CP [9,13,33,[35][36][37], while in others, no differences were found [10-12, 14-17, 29, 32]. However, most of the latter studies showed an increased but not significant rate of postoperative pancreatic fistulae compared to distal pancreatectomy (21.4-44% for CP vs. 14-29% for distal pancreatectomy); significance may not have been reached due to the small number of patients analyzed [11,15,17,29,32]. Only a few statistically powered studies have shown that there is no difference between CP and distal pancreatectomy in terms of rates of postoperative pancreatic fistula development [10,12,14,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crippa et al [19] called a distal pancreatectomy in which the pancreas was divided at the level of the SMV-SV-PV confluence an ''extended'' distal pancreatectomy as opposed to a central pancreatectomy. Thus, we may specifically title Warshaw procedure used for this PpSpTPD as an ''extended'' Warshaw procedure, because the pancreas also was divided at the level of the SMV-SV-PV confluence, and the splenic artery and vein were securely controlled at the origin of the vessels [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of laparotomy, an inverted L incision was usually made for surgical exploration, but only a small upper midline laparotomy (8-10 cm) was required for hepaticojejunostomy and duodenojejunostomy in the case of a laparoscopic approach. We regarded the whole surgical procedure as a combination of two different surgeries: SpDP with segmental resection of the splenic vessels (the so-called Warshaw's procedure) [9], and PpPD. After complete resection of the whole pancreas ( Fig.…”
Section: Operative Techniquementioning
confidence: 99%